2017
DOI: 10.1002/1878-0261.12054
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase activity mediates acquired resistance towards structurally diverse HSP90 inhibitors

Abstract: Heat shock protein 90 (HSP90) regulates multiple signalling pathways critical for tumour growth. As such, HSP90 inhibitors have been shown to act as effective anticancer agents in preclinical studies but, for a number of reasons, the same effect has not been observed in the clinical trials to date. One potential reason for this may be the presence of de novo or acquired resistance within the tumours. To investigate mechanisms of resistance, we generated resistant cell lines through gradual dose escalation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…17-AG enhanced activity of MAPK pathway inhibitors, vemurafenib and trametinib, in induction of apoptosis that might result from concurrent inhibition of IRE1α and ERK1/2 activities [89]. Interestingly, it was also demonstrated that prolonged treatment with 17-AAG could develop resistance to a spectrum of structurally distinct inhibitors of HSP90, and acquired resistance could be overcome by HDAC inhibitors [109].…”
Section: Benzoquinone Inhibitorsmentioning
confidence: 99%
“…17-AG enhanced activity of MAPK pathway inhibitors, vemurafenib and trametinib, in induction of apoptosis that might result from concurrent inhibition of IRE1α and ERK1/2 activities [89]. Interestingly, it was also demonstrated that prolonged treatment with 17-AAG could develop resistance to a spectrum of structurally distinct inhibitors of HSP90, and acquired resistance could be overcome by HDAC inhibitors [109].…”
Section: Benzoquinone Inhibitorsmentioning
confidence: 99%
“…CD44+/Sca1+ cells that were shown to have enhanced radioresistance and increased HSF1 activity were also found to be induced after radiation treatment [107,153,154]. HSF1 may coordinate resistant cancer cell properties through chromatin organization in cooperation with HDACs or other DNA-modifying complexes, such as MTA1, each of which have also been linked to resistance to cytotoxic compounds [155,156]. Alternatively, HSF1 has also been shown to promote resistance to cytotoxic therapies through its pro-glycolysis metabolic regulatory activities [51].…”
Section: Resistance and Recurrencementioning
confidence: 99%
“…However, only transient responses to HSP90 inhibitors have been observed in patients with mutant KRAS tumors . This is suggestive of the development of acquired resistance to HSP90 inhibitors by cancer cells . Various mechanisms have been reported to be involved in acquired resistance of cancer cells to HSP90 inhibition .…”
Section: Introductionmentioning
confidence: 99%
“…This is suggestive of the development of acquired resistance to HSP90 inhibitors by cancer cells . Various mechanisms have been reported to be involved in acquired resistance of cancer cells to HSP90 inhibition . For example, reactivation of the ERK‐p90RSK‐mTOR signalling pathway mediates acquired resistance of KRAS mutant non‐small cell lung cancer (NSCLC) to the HSP90 inhibitor ganetespib, whereas the secondary Y142N mutation in HSP90α confers acquired resistance of MDA‐MB‐231 breast cancer cells to the HSP90 inhibitor PU‐H71 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation